Vertical axis wind turbine performance prediction: a new approach to the double multiple streamtube model - Melício, Rui (2012)
The vertical axis wind turbines (VAWT) have been suffering an increased acceptance for urban wind turbines integration in the future smart grid for decentralized generation (DG). The VAWT have several advantages over the more conventional horizontal axis wind turbines (HAWT): the smaller number of components; low sound emissions; their insensitivity to fast changes in wind flow direction; a lower architectural visual impact; the ability to operate closer to the ground; and others. But, the VAWT aerodynamic performance is more complex to simulate and predict due to its three dimensional operation. Several mathematical models have been presented to predict the VAWT performance, such as the double multiple streamtube (DMS) model. With the aim of presenting a tool to ease the study of complex shaped VAWTs, being at the same time able to be easily integrated in computational design tools, a new approach to the DMS model is presented in this paper.